COVID-19 vaccine hesitancy and associated factors among infertile couples undergoing assisted reproductive treatment - Wang, Xinyan; Wang, Huiyan; Du, Aijun; Wang, Junchao; Shi, Jie; Zhang, Yunshan; Zhang, Yinfeng; Ma, Junfang; Meng, Wenjia; Lv, Jiabei; Luo, Haining (Frontiers in Immunology, 2022)
Although periconception vaccination is important to maternal and neonatal health, little is known about the COVID-19 vaccine hesitancy among infertile couples seeking fertility treatment. Thus, we conducted this survey among infertile patients in a reproductive medicine center, between September 2021 and December 2021, to estimate the prevalence of COVID-19 vaccine hesitancy and its influencing factors. Information was collected through face-to-face interviews among volunteers. Among the 987 included interviewees, 17.33% reported hesitancy in primary vaccination, 25.63% reported hesitancy in booster vaccination, and 32.32% delayed the primary vaccination. Hesitancy in primary vaccination was associated with unexplained infertility (OR: 1.77, 95% CI: 1.05-2.98), ongoing IVF treatment (OR: 2.17, 95% CI: 1.22-3.89), concerns for vaccine safety (OR: 4.13, 95% CI: 2.66-6.42), effectiveness (OR: 1.62, 95% CI: 1.15-2.28), and influence on pregnancy (OR: 2.80, 95% CI: 1.68-4.67). These factors were also associated with hesitancy in booster vaccination. Delay of the primary vaccination was inversely associated with a college or above degree (OR: 0.49, 95% CI: 0.27-0.87), previous history of influenza vaccination (OR: 0.67, 95% CI: 0.46-0.98), and was positively associated with concerns for the influence on pregnancy (OR: 7.78, 95% CI: 5.01-12.07). It is necessary to carry out targeted education program by health professionals to publicize the benefits of periconception vaccination, and to reduce the resistance to COVID-19 vaccine among infertile couples.